Ornithology of the Kelabit Highlands of Sarawak, Malaysia - Sheldon, Frederick H.; Mustafa, Abdul Rahman; Moyle, Robert G.; Tay, G.K; Brown, C.E (National University of Singapore, 2013)
The Kelabit Highlands played a key role in the development of modern Bornean ornithology. The Highlands consist of a plateau at 1000-1200 m with substantial wet rice paddy and surrounding taller mountains. These physical features lead to an unusual combination of montane, lowland, and migratory birds. This avifauna was studied in the 1940s to 1950s by two ornithologists whose collaboration helped usher in the modern era of Bornean ornithology: Tom Harrisson of the Sarawak Museum and Dean Amadon of the American Museum of Natural History. We examine their collaboration and explain how these men contributed to Bertram Smythies' milestone book, The Birds of Borneo (1960). Although the roles of Harrisson and Smythies in Bornean ornithology are well known, the contribution of Dean Amadon is not generally appreciated, and we clarify it. In the process, we also consider modern work on the Kelabit avifauna, including our own expedition in 2011, and the current status of Kelabit birds and issues relating to their conservation and potential for further study